PENGARUH KEPRIBADIAN DAN KEMAMPUAN INTELEKTUAL TERHADAP KOMPETENSI GURU DI SMKN 3 KOTA BENGKULU - Sentia Rapika; Anggri Puspita Sari (Management Insight: Jurnal Ilmiah Manajemen, 2017)
The purposes of this study examines the effect of personality and intellectual ability on teacher competence in SMKN 3 Bengkulu city. This research was conducted in SMKN 3 Bengkulu City with the object of research is permanent teachers or civil servants. The sample used in this study was 74 respondents using purposive sampling technique. Data analysis technique using multiple regression analysis and using SPSS 17.0 sofware. Research design using survey explanatory, the method in this study using factor analysis to test the validity of the data and using Cronbach's alpha to test the reliability of the data. The results of this research shows that the personality and intellectual ability partially have positive and signifikan effect on the teacher competence. Personality and intellectual ability simultaneously have significant effect on the teacher competence in SMKN 3 Bengkulu city.Keywords: personality, intellectual ability, teacher competence.